THE ROLE OF ASSET DEPRECIATION IN THE COMPANY'S FINANCIAL INDICATORS AND ITS IMPROVEMENT - Sayfullayev Mexroj Sayfullayevich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
In this article, the role of asset impairment losses in the company's financial indicators and proposals for its improvement are developed.